The second sleep [compact disc, unabridged] - Harris, Robert, 1957- (Penguin Random House, 2019)
1468. A young priest, Christopher Fairfax, arrives in a remote Exmoor village to conduct the funeral of his predecessor. The land around is strewn with ancient artefacts--coins, fragments of glass, human bones--which the old parson used to collect. Did his obsession with the past lead to his death? Fairfax becomes determined to discover the truth.